Mild iron deficiency anaemia during pregnancy and lactation in guinea pigs alters amplitudes and auditory nerve velocity, but not brainstem transmission times in the offspring's auditory brainstem response. (January 2014) - Jougleux, Jean-Luc; Rioux, France M.; Church, Michael W.; Fiset, Sylvain; Surette, Marc E.
<x content-type="archive" xml:space="preserve">Abstract</x> Objectives It is well known that postnatal/early childhood iron deficiency (ID) anaemia (IDA) adversely affects infants' cognitive development and neurophysiology. However, the effects of IDA during gestation and lactation on the offspring are largely unknown. To address this health issue, the impact of mild IDA during gestation and lactation on the offsprings' neural maturation was studied in the guinea pig, using auditory brainstem responses (ABRs) latencies and amplitudes. Methods Female guinea pigs (n = 10/group) were fed an iron sufficient (ISD) or deficient diet (IDD) (144 and 11.7 mg iron/kg) during the gestation and lactation periods. From postnatal day (PNd) 9 onward, the ISD was given to both groups of weaned offspring. The offsprings' ABRs were collected on PNd24 using a broad range of stimulus intensities in response to 2, 4, 8, 16, and 32 kHz tone pips. Results Although the IDA siblings (n = 8) did not differ in brainstem transmission times (BTTs) compared to the IS siblings (n = 8), they showed significant delayed peak I latency at 100 and 80 dB, respectively. Additionally, significantly higher ABR wave amplitudes were observed in the IDA female offspring between 35 and 50 dB (4 kHz), a phenomenon suggestive of a neural hyperactivity (hyperacusis). Discussion In support to our previous findings, the present results indicate that a mild IDA during gestation and lactation can have detrimental effects on early development of the offsprings' hearing and nervous systems, particularly on neural synchrony and auditory nerve conduction velocity, but not on BTT.